Detection of Coxiella burnetii in cows’, goats’, and ewes’ bulk milk samples using polymerase chain reaction (PCR) - Hayriye Yesim Can; Mehmet Elmalı; Alper Karagöz (Mljekarstvo)
Q fever is a widespread zoonotic disease that is caused by obligate intracellular bacteria, Coxiella burnetii. This study was planned to determine the prevalence of C. burnetii in cows’, goats’, and ewes’ bulk milk (BM) samples using PCR and to confirm positive results by DNA sequencing. A total of 150 BM samples (50 samples of each cows’, goats’, and ewes’ milk) collected from 15 randomly selected dairy farms in Hatay province were analyzed. The BM samples were taken between January 2012 and July 2013. Bacterial DNA was extracted directly from milk samples. Nine of the BM samples (6 %) were PCR positive; five from cows’ BM, two from ewes’ BM, and two from goats’ BM. Bacterial DNA was detected in 3 of 15 (20 %) dairy farms. Positive results were confirmed by DNA sequencing. The sequencing results of Coxiella DNA extracted from cows’, goats’, and ewes’ milk samples were consistent with the reference strain with 100 %, 99.7 %, 99.8 % homology, respectively. BM samples were found to be contaminated with C. burnetii; therefore, taking hygienic measures is necessary for food safety and public health.